2019
DOI: 10.1016/j.waojou.2018.11.005
|View full text |Cite
|
Sign up to set email alerts
|

1H NMR-based metabolomic study of metabolic profiling for pollinosis

Abstract: Background Allergic rhinitis is the main symptom of pollinosis, relieved by non-specific treatment universally. This study aimed to find the changes of serum metabolites between the seizure and remission periods of pollinosis and provide assistance in the diagnosis and/or therapy. Methods Metabonomics based on 1 H nuclear magnetic resonance (NMR) was used to study the 37 serum samples of pollinosis patients. Results … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
13
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 32 publications
2
13
0
1
Order By: Relevance
“…This has been identified as a biomarker of asthma, along with glutamine and histidine, 29 and all three altered at seizure stage of pollinic patients. 30 On the other hand, L-tryptophan, L-arginine and L-kynurenine were significantly increased on the apical compartment of ALIcultured Calu-3 cells after Der p 1 exposure but not on the basolateral one, compared to both, control and Ole e 1-exposed cells.…”
Section: Annotation and Identification Of Metabolites Released By Ali-cultured Calu-3 Cells After Allergen Exposure During Barrier Establmentioning
confidence: 81%
See 1 more Smart Citation
“…This has been identified as a biomarker of asthma, along with glutamine and histidine, 29 and all three altered at seizure stage of pollinic patients. 30 On the other hand, L-tryptophan, L-arginine and L-kynurenine were significantly increased on the apical compartment of ALIcultured Calu-3 cells after Der p 1 exposure but not on the basolateral one, compared to both, control and Ole e 1-exposed cells.…”
Section: Annotation and Identification Of Metabolites Released By Ali-cultured Calu-3 Cells After Allergen Exposure During Barrier Establmentioning
confidence: 81%
“…Methionine plays an important role in the synthesis of proteins involved in the immune response. This has been identified as a biomarker of asthma, along with glutamine and histidine, 29 and all three altered at seizure stage of pollinic patients 30 …”
Section: Discussionmentioning
confidence: 99%
“…Zhou et al. studied serum samples from pollinosis patients using NMR-based metabolic patients and found that pollinosis could alter the metabolic profile of energy, amino acid and lipid in patients, which may be diagnostic and/or prognostic markers in patients with hay fever ( 51 ). Adamko et al.…”
Section: Discussionmentioning
confidence: 99%
“…According to published studies, L-threonine, a kind of amino acid, was reduced in SLE plasma compared with HCs. 15 Moreover, Zhou et al 14 revealed that SLE sera samples were characterized by decreased Beta-alanine using 1 H NMR spectroscopy-based metabolomics. Consistently with their results, the reduced serum L-threonine and Beta-alanine were detected in our study indicating our results were solid and stable.…”
Section: Discussionmentioning
confidence: 99%